IMPLEMENTASI PENGGUNAAN FINANCIAL TECHNOLOGY QRIS BANK BPD BALI CABANG NEGARA UNTUK GENERASI X DI PASAR UMUM BAHAGIA - I Gusti Ayu Kade Santika Dwi Antari; Gede Pradiva Adiningrat; Upayana Wiguna Eka Saputra (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The development of financial technology has driven a transformation in Indonesia's payment system, one of which is through the implementation of QRIS (Quick Response Code Indonesian Standard). This initiative aims to create efficient and inclusive cashless transactions. This study aims to analyze the implementation of QRIS by Bank BPD Bali, Negara Branch, among Generation X merchants at Pasar Umum Bahagia, and to identify the obstacles encountered in the adoption process. Employing a descriptive qualitative approach using the AIDA model (Awareness, Interest, Desire, Action), the study involved field observations, in-depth interviews with Generation X merchants, and supporting documentation. The findings indicate that although most merchants already have bank accounts and are registered in the QRIS system, only a small number actively use the service. The main barriers identified include limited access to technological devices, unstable internet connections, and low trust in the security of digital systems. The study recommends continuous digital education, infrastructure improvement, and more personalized and repeated outreach by the bank to enhance QRIS adoption among traditional market merchants, particularly those from Generation X.